DEVELOPMENT OF ARTILLERY TACTICS IN LOCAL AND LARGE-SCALE CONFLICTS - Кольцов, Р.Ю.; Левінськова, Н.В.; Кучер, А.О. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2025)
The article is devoted to the study of the development of artillery tactics in the context of local and large-scale armed conflicts, taking into account the experience of the world's leading armies and the features of modern warfare. Historical and modern approaches to the organization and use of artillery are analyzed, including methods of massive fire damage, high-precision shooting, maneuvering with fire and forces, as well as interaction with other branches of the armed forces. The impact of the development of reconnaissance and strike complexes, automated fire control systems and modern reconnaissance means on the effectiveness of artillery operations in various types of combat operations is highlighted.The article provides a comparative analysis of artillery tactical techniques in local low-intensity conflicts and large-scale military campaigns. The role of artillery in providing fire superiority and supporting offensive and defensive operations, as well as in conducting counter-battery combat, is revealed. Special attention is paid to the influence of geographical and climatic conditions on the use of artillery and the peculiarities of logistical support in different conditions.Scientific and practical approaches to improving artillery tactics are analyzed, in particular, based on the experience of wars of recent decades (Iraq, Afghanistan, Syria, the war in Ukraine) and recommendations of NATO military research centers and leading domestic scientific institutions. Ways of integrating artillery units into the system of network-centric operations and the use of unmanned aerial vehicles for fire correction are considered.Based on the results of the study, proposals are formulated to increase the effectiveness of artillery operations in modern conditions, improve the personnel training system, and introduce the latest technologies in reconnaissance, fire control, and fire correction. Recommendations are proposed for adapting tactical artillery solutions to the conditions of hybrid and asymmetric military conflicts, as well as creating a flexible doctrine of artillery use that can function effectively in both local and large-scale combat operations.

Стаття присвячена дослідженню розвитку артилерійської тактики у контексті локальних та масштабних збройних конфліктів, із урахуванням досвіду провідних армій світу та особливостей сучасного ведення війни. Проаналізовано історичні та сучасні підходи до організації і застосування артилерії, включно з методами масованого вогневого ураження, високоточної стрільби, маневру вогнем та силами, а також взаємодії з іншими родами військ. Висвітлено вплив розвитку розвідувально-ударних комплексів, автоматизованих систем управління вогнем і новітніх засобів розвідки на ефективність артилерійських операцій у різних типах бойових дій.У статті наведено порівняльний аналіз тактичних прийомів артилерії у локальних конфліктах низької інтенсивності та масштабних воєнних кампаніях. Розкрито роль артилерії у забезпеченні вогневої переваги та підтримки наступальних і оборонних операцій, а також у веденні контрбатарейної боротьби. Окремо приділено увагу впливу географічних та кліматичних умов на застосування артилерії та особливостям логістичного забезпечення в різних умовах.Проаналізовано наукові та практичні підходи до удосконалення артилерійської тактики, зокрема на основі досвіду воєн останніх десятиліть (Ірак, Афганістан, Сирія, війна в Україні) та рекомендацій військових дослідних центрів НАТО і провідних вітчизняних наукових установ. Розглянуто шляхи інтеграції артилерійських підрозділів у систему мережоцентричних операцій та застосування безпілотних літальних апаратів для коригування вогню.За результатами дослідження сформульовано пропозиції щодо підвищення ефективності артилерійських дій у сучасних умовах, удосконалення системи підготовки особового складу, впровадження новітніх технологій у розвідку, управління та коригування вогню. Запропоновано рекомендації для адаптації тактичних рішень артилерії до умов гібридних та асиметричних воєнних конфліктів, а також створення гнучкої доктрини застосування артилерії, здатної ефективно функціонувати як у локальних, так і у масштабних бойових діях.
РОЗВИТОК АРТИЛЕРІЙСЬКОЇ ТАКТИКИ У ЛОКАЛЬНИХ ТА МАСШТАБНИХ КОНФЛІКТАХ
Keywords: артилерія; артилерійська тактика; локальні конфлікти; масштабні конфлікти; вогнева підтримка; контрбатарейна боротьба; автоматизовані системи управління вогнем; розвідка; високоточна зброя; artillery; artillery tactics; local conflicts; large-scale conflicts; fire support; counter-battery warfare; automated fire control systems; reconnaissance; high-precision weapons